DIFFERENTIAL COST ANALYSIS IN THE DECISION TO MAINTAIN OR DISCONTINUE A PRODUCT. (Case Study at PT. Modern Keramik Jaya in Surabaya) - Nur Halimatus Fatmasari; Diana Zuhro; Sutini Sutini; Annisa Rachmawati; Achmad Daeng GS (PT. Mawadaku Sukses Solusindo, 2026)
This research focuses on soap dispenser products which experienced a decline in production and sales volume, resulting in declining profits from period to period, with the aim of finding out how the company should make decisions when using differential cost analysis. The research method used is descriptive qualitative, the nature of which is to reveal and discuss problems by explaining, interpreting and describing the conditions and events that occurred when the research was taking place and a conclusion was drawn. The types of data used are primary data and secondary data collected by observation techniques, interviews, online data search methods, documentation, and literature studies. The object used in this study is PT. Modern Keramik Jaya in Surabaya. The study used production data and sales data for September 2017-April 2018. From the results of the data, it can be seen that there is a problem of decreasing production volume and sales of one of the products, resulting in the company experiencing losses from time to time. Therefore, an analysis of which decision is more profitable is to continue the soap dish product or stop it. The company's policy is to make the decision to stop the production of ceramic soap dishes based only on the profit / loss report without any further analysis because in the period September 2017-April 2018 there was a continuous decline in sales. In addition, the company also experienced a loss of Rp.(222,524,000) in the period September-December 2017 and Rp.(143,486,000) in the period January-April 2018. Based on the results of the differential cost analysis in September 2017-April 2018, the company should maintain the production of soap dispensers, this is because there are unavoidable fixed costs that are greater than the loss of contribution margin, so that by maintaining the production of soap dispensers, the company will reduce the losses experienced by the company. To overcome the decline in production, the company should improve the quality of its products or create new designs that can attract more consumers. Meanwhile, to overcome the high production costs, the company should emphasize spending production costs as minimally as possible. This study aims to analyze the financial performance of PT. Bank Jatim using the common size method based on its financial statements for the period 2023-2024. The research adopts a descriptive quantitative approach with secondary data derived from audited financial reports. The common size method was applied to both the balance sheet and income statement to evaluate changes in the proportion of assets, liabilities, equity, revenues, and expenses relative to their totals.